Gerakan Salafiyyah di Pondok Pesantren Dhiya’ussalaf Muara Enim Sumatera Selatan - Muhammadin Muhammadin (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2015)
This article is derived from the results of research that examines the understanding and factors underlying the emergence of Salafiyyah movement in Dhiya'ussalaf boarding school. This article concludes that the understanding pattern of Salafiyyah movement in Dhiya'ussalaf boarding school has the act based on Sunnah. The act exemplified by the tabi'in has a missionary with tashfiyah principle in the sense of purification of Islam including bid’ah and hizbiyyah or harakiyyah. In addition, the school has principle in the sense of propaganda by fostering people to be a man who is able to live independently and to be perfectly servitude to God.